Risks Associated with the Market Behaviour of Bulgarian Industrial Enterprises - Ivanova, Z.S. (Економічний вісник Донбасу, 2015)
Bulgarian industrial enterprises operate in extremely competitive global markets. This inevitably increases the likelihood of the occurrence of a number of risks and increases their level of risk exposure. The purpose of this article is to highlight some of the main risks accompanying the demonstration of a certain market behaviour of Bulgarian industrial enterprises, to present the results of analyzing the risk exposure and the problem areas in their market behaviour, and to justify the opportunities for affecting the risks.